A new approach to quantifying stratigraphical resolution: application to global stratotypes. (28th September 2016) - Melchin, Michael J.; Sheets, H. David; Mitchell, Charles E.; Fan, Junxuan
Abstract : Horizon annealing (HA) provides a method to order all horizons in a chronostratigraphic data set, including marker beds and isotopic excursions, as well as horizons that lack exact local markers (such as taxon first appearances) and are, thus, constrained only by local stratigraphical order. Global stratotype section and point (GSSP) levels placed within an HA composite succession can be precisely correlated with levels in all other sections in the composite that span the same interval. We present two approaches to the quantitative assessment of the uncertainty or error in the placement of horizons within the composite section: a permutation method (jackknife analysis) and a sensitivity analysis (the relaxed fit curve). From jackknife analysis, we calculate a standard deviation ( σ ) of the variation in horizon placements and estimate the 95% confidence interval of the variation in horizon placement within the composite. We also directly assess the relative stability of event positions using the results of the jackknife. These approaches provide an objective method for assessing the relative strengths of GSSP candidates, in which we prefer those sections and horizons that are the most precisely controlled in the HA composite. Integration of biostratigraphical, chemostratigraphical and lithostratigraphical marker horizons into the HA process markedly improves levels of constraint within the composite compared to biostratigraphical data alone. In a temporally scaled composite, the 95% confidence intervals on horizon placements could be used to estimate temporal resolution. In our study, we estimate that the average temporal resolution is approximately 319 kyr, which approaches the range of that needed to test hypotheses of orbitally driven cyclicity.